Upaya Peningkatan Kualitas Pelayanan pada Kareta Api Bandara (Minangkabau Ekspres) di Provinsi Sumatera Barat - Beni Rahmat; Aldri Frinaldi (Policy, Law and Political Research Center, 2022)
This study aims to analyze the Efforts to Improve Service Quality at Airport Trains (Minangkabau Ekspres) in West Sumatra Province. This type of research is semi-qualitative. The results of this study indicate that an analysis of several aspects for efforts to improve service quality including tangible aspects (tangible) there are still facilities that need improvement, from the aspect of empathy (empathy) some employees in providing services still do not understand the needs of service users, from the aspect of responsiveness (responsiveness). ) namely the response to public complaints is still slow and unresponsive, from the aspect of reliability (reliability) the services provided are quite accurate but there are still delays, and the last aspect is assurance, namely supervision is not optimal and lack of greetings and greetings. Constraints found in Efforts to Improve Service Quality on Airport Trains (Minangkabau Express) in West Sumatra Province include facilities and infrastructure that are damaged or not functioning properly, events that cannot be predicted significantly, lack of public understanding, apparatus resources are still lacking. not yet competent.